Gaya Kepemimpinan Transformasional Leadership Kepala Ruangan Berhubungan Interprofessional Collaboration Perawat - Fitriyani, Elsa; Febriani, Nelly (Tribhuwana Tunggadewi University, 2025)
Transformational leadership style is very effective in improving interprofessional collaboration in hospitals by providing a clear vision, encouraging open communication, valuing each profession, facilitating interprofessional meetings, and ensuring continuous development, transformational leaders can create a collaborative and productive work environment. The purpose of the study was to determine the relationship between the transformational leadership style of the head of the room in improving team collaboration in the inpatient room of Khidmat Sehat Afiat (KISA) Hospital, Depok City.This study used a quantitative method with a chi-square correlation test with a cross-sectional approach. Sampling using Accidental sampling sample amounted to 108 employees.The results data obtained through the Multifactor Leadership Questionnaire, Assessment of Interprofessional Team Collaboration Scale (AITCS) obtained that there is a significant relationship between the transformational leadership style of the head of the room with the level of team collaboration p-value 0.002. It is expected that future researchers will develop data by expanding the population, adding variables and different measuring instruments. It is also expected that the hospital will develop a transformational leadership training program for the head of the room to improve team performance